31 murders: following the trail of serial sex killer Earle Nelson - Esau, Alvin A. J. (Exposit, 2024)
""Many decades before Ted Bundy roamed the country there was serial killer Earle Nelson. During the 1920s, this geographically mobile serial killer roamed from city to city. His modus operandi involved getting into a house by pretending to be a person looking for a room to rent or inspecting a house that was for sale, and then strangling the landlady, often followed by having sex with the dead body. Robbery was frequently a secondary motive. After Nelson was captured in Canada in 1927, it was commonly reported that he had killed 21 women and a baby during the 1926-27 period. But were these the only cases linked to him? The author examines an additional nine unsolved murders of landladies, two of which have never been dealt with in previous literature. Based on decades of archival research, the author examines all 31 murders, relying on primary sources when available and a wide variety of secondary sources. For each murder, the book provides biographical sketches of the victim, outlines the police investigation and the various suspects, and covers any subsequent attempts to link Nelson to the crime by identification evidence of witnesses or by fingerprints."-Provided by publisher"--